Leukemia in children: necessities and integral intervention based on the person-centered model - Fernández de Córdoba Martínez, Esther (2018)
Considering the high incidence of leukemia in children, this paper proposes the performance lines to an adequate psychopedagogical intervention. First, we proposed detect the real necessities that come from the disease in the different areas ofthe person. Based on that, the topics to be taken into consideration are shown in an intervention from the person-centered model, which analyses professionals, services and the involved resources.